THE INFLUENCE OF MOTIVATION AND CONSUMER ATTITUDE ON ONLINE SHOP PURCHASE DECISION - Lendo, Ratyh Rizka (Universitas Sam Ratulangi, 2013)
Improving the welfare of human life require an effort to fulfill the needs of life. This globalization era characterized by a wide range of competition in all fields, including advanced business and technology competition resulted in increasing needs and influence the behavior of consumers to buy a product with the increasing human technological development required to keep abreast of current technology to keep up. Online shopping is a process of buying goods or services from sellers who sell on the internet. Consumers can purchase various items from online stores. Many people prefer online goods because of its simplicity, saving time and comfort. The purpose of this study was to find the effect of motivation and the effect of consumer attitude on online shop purchase decision. This research is a quantitative research that used causal type of research.Â Multiple regression analysis is a statistical technique that used in this research. The population of this research is Student College in International Business Administration batch 2009, with sample 61 respondents. The result of this research shows that motivation has no significant effect on purchase decision, and consumer attitude has significant effect on purchase decision. Keywords: motivation, consumer attitude, purchase decision